209k views
2 votes
Evaluate the expression for h=(-4)
-h=___

User Zart
by
5.4k points

2 Answers

0 votes
Answer: h= -4

Explanation: You just simply remove the parentheses to get the solution to this problem
User Torrell
by
5.7k points
0 votes

Answer:

h= -2

Explanation:

How to solve your question

Your question is

=

(

4

)

h=(-4)-h

h=(−4)−h

Solve

1

ℎ − 4

h=-h-4

h=−h−4

2. Subtract from both sides of the equation

3. Simplify

4. Divide both sides of the equation by the same term

5. Simplify

Solution

ℎ = −2

User JeyasuryaUR
by
6.9k points